2014
DOI: 10.1021/cm500914b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Size on Framework Defects and Water Uptake in Fluoride Mediated Silicalite-1

Abstract: The relationship between framework defects and crystal size in fluoride mediated silicalite-1 was investigated through nitrogen physisorption, X-ray diffraction, and vapor adsorption of ethanol and water on samples with crystal sizes ranging from 0.4 to 30 μm in the b direction of the silicalite-1 crystals. X-ray diffraction reveals a shift in the lattice system from a predominantly monoclinic phase in smaller crystals to an orthorhombic phase in the larger crystals. 29 Si MAS studies reveal minimal difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…177 Permporometry, flux of molecules larger than zeolite pores and the ratio of single gas permeance, and other methods have been used to characterize defects. [206][207][208][209] These effects have been incorporated in some of the modeling studies by determining the permeation through the defects as a combination of Knudsen diffusion and Poiseuille flow. 210,211 A general pore network model has also been developed to account for the flux through intercrystalline pores.…”
Section: Other Factorsmentioning
confidence: 99%
“…177 Permporometry, flux of molecules larger than zeolite pores and the ratio of single gas permeance, and other methods have been used to characterize defects. [206][207][208][209] These effects have been incorporated in some of the modeling studies by determining the permeation through the defects as a combination of Knudsen diffusion and Poiseuille flow. 210,211 A general pore network model has also been developed to account for the flux through intercrystalline pores.…”
Section: Other Factorsmentioning
confidence: 99%
“…It was found that the stretching vibrational mode at 3448 cm −1 (or the bending one at 960 cm −1 ) due to silanol groups is intensified by forming PMS structure during the process and remain much stronger than that of the parent silicalite‐2 by forming h‐nanoplatelets after long time treatment (over 192 h). This indicates formation of a lot of silanol sites or internal silanol deficiencies on the surface or the bulk structure of the formed h‐nanoplatelets …”
Section: Resultsmentioning
confidence: 99%
“…Among pentasil zeolite families, the all‐silica (aluminum‐free) MFI‐type silicalite‐1 and its structure analog MEL‐type silicate‐2 have attracted a great deal of concern. Due to thermal/structural stability, medium pore opening (0.51–0.56 nm), and hydrophobicity with tunable amount of internal silanol groups (depending on synthesis approach) but lacking solid acidity, they are promising adsorbents in particular for concentrating dilute organics from aqueous solution in biofuel production process and for removing trace amount of organic contaminants in water treatment processes . Silicalite‐2, characteristic of two identical orthogonally intersecting channels, is likely more diffusion‐favored as compared to silicalite‐1 containing the zigzag‐crossing straight and side‐pocket channels .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silanol defects are easily formed due to the absence of the framework Si usually under alkaline synthesis conditions (Figure 2). 20 The increased amount of hydroxyl groups by CNF-mediated synthesis possibly causes a more notable influence toward the adsorption of organic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…3 These properties make it promising, in particular, for concentrating dilute organics from aqueous solution in the biofuel production process 19,20 or selectively removing low concentration of solvent pollutants from the water environment such as methyl tert -butyl ether (MTBE) in underground water, the trace residual n -nitrosodimethylamine (NDMA) in reclaimed water, and so forth. 2123 Herein, we attempted to use CNF as a meso/macroporogen additive in the synthesis of silicalite-1.…”
Section: Introductionmentioning
confidence: 99%